Association between remnant cholesterol levels and reversion to normoglycemia from prediabetes: a 5-year longitudinal cohort study of Chinese non-obese adults - Liu, Wei; Jian, Wenjing; Lin, Suina; Huang, Zhenhua (Frontiers in Endocrinology, 2025)
PurposeThe primary objective of this study is to explore the relationship between remnant cholesterol (RC) levels and the reversion to normoglycemia in non-obese Chinese individuals with prediabetes.MethodsTo achieve this goal, we conducted a retrospective cohort study involving 8,109 non-obese prediabetic participants in China, using the Cox proportional hazards regression model to analyze the correlation between RC and the likelihood of returning to normoglycemia.ResultsThe results indicate a significant negative correlation between RC levels and reversion to normoglycemia (HR=0.49, 95% CI: 0.47-0.52). Specifically, as RC quartiles increase, the probability of reverting to normoglycemia significantly decreases, with participants in the highest quartile having a 51% lower likelihood of recovery compared to those in the lowest quartile. Furthermore, we identified a nonlinear relationship between RC and the reversion to normoglycemia, with 1.10 mmol/L established as the inflection point. When RC levels are below this threshold, decreasing RC significantly increases the likelihood of recovery. To further validate the robustness of our findings, we conducted sensitivity and subgroup analyses, all of which support the reliability of the main results.ConclusionThere exists a significant negative and nonlinear relationship between RC levels and the reversion to normoglycemia in non-obese Chinese prediabetic patients. This suggests that lowering RC levels may play an important role in reversion to normoglycemia from prediabetes.